Meta-Analysis: Effectiveness of Web-Based Intervention to Increase Physical Activity in Older People - Gina Fazrina; Hapsari Cahyaningrum (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: The increasing global population of older people and the trend of life expectancy make the discussion of physical activity an urgent urgency, given its role in preventing various non-communicable diseases and increasing life expectancy. Web-based intervention is believed to be an intervention that can change habits related to physical activity in older people. This study aimed to find out whether web-based intervention is effective in increasing physical activity for older people.Subjects and Method: This research is a meta-analysis based on the PRISMA flow diagram. The article search process is carried out through journal databases, in the form of: Google Scholar, PubMed, and ResearchGate. Keywords to search for articles are: